The impact of care pathways for patients with proximal femur fracture: rationale and design of a cluster-randomized controlled trial - Vanhaecht, Kris (BioMed Central, 2012)
BACKGROUND: Proximal femur fracture (PFF) is associated with considerable morbidity and mortality. The European Quality of Care Pathway (EQCP) study on PFF (NCT00962910) was designed to determine how care pathways (CP) for hospital treatment of PFF affect consistency of care, adherence to evidence-based key interventions, and clinical outcome. METHODS/DESIGN: An international cluster-randomized controlled trial (cRCT) will be performed in Belgium, Ireland, Italy and Portugal. Based on power analyses, a sample of 44 hospital teams and 437 patients per arm will be included in the study. In the control arm, usual care will be provided. Experimental teams will implement a care pathway which will include three active components: a formative evaluation of quality and organization of the care setting, a set of evidence-based key interventions, and support of the development and implementation of the CP. Main outcome will be the six-month mortality rate. DISCUSSION: The EQCP study constitutes the first international cRCT on care pathways. The EQCP project was designed as both a research and a quality improvement project and will provide a real-world framework for process evaluation to improve our understanding of why and when CP can really work. TRIAL REGISTRATION NUMBER: NCT00962910